Postural control and functional balance in individuals with diabetic peripheral neuropathy - Fortaleza, Ana Claudia de Souza [UNESP]; Chagas, Eliane Ferrari [UNESP]; Ferreira, Dalva Minonroze Albuquerque [UNESP]; Mantovani, Alessandra Madia [UNESP]; Barela, José Angelo [UNESP]; Chagas, Eduardo Federighi Baisi [UNESP]; Fregonesi, Cristina Elena Prado Teles [UNESP] (Universidade Federal de Santa Catarina, 2013)
A Neuropatia diabética periférica (NDP) cursa com redução somatossensitiva que pode levar a alterações no controle postural. O objetivo do estudo foi avaliar o controle postural na postura ereta, em diferentes condições, e o equilíbrio funcional em indivíduos com NDP, correlacionar os resultados obtidos na avaliação do controle postural com os valores do teste do equilíbrio funcional e comparar os resultados obtidos no grupo neuropata com o grupo controle, verificando as possíveis diferenças entre as condições de avaliação em ambos os grupos. Participaram do estudo 13 mulheres com NDP (GN) e 17 mulheres não diabéticas (GC). A avaliação do controle postural foi realizada por cinemetria nas condições: olhos abertos (OA), olhos fechados (OF) e semi tandem (ST). Após processamento no MATLAB, foram geradas as variáveis: amplitude média de oscilação (AMO) na direção ântero-posterior (AP) e médio-lateral (ML); e velocidade média de oscilação (VMO) na direção AP e ML. O equilíbrio funcional foi avaliado pelo Timed Up and Go Test. Houve diferença significante entre os grupos (p<0,005) na AMO-AP OA e OF, AMO-ML of e ST e VMO-ML ST. Houve diferença entre as condições OA e ST (p<0,005) e of e ST (p<0,005) para as variáveis AMO-ML e VMO-ML, com maior prejuízo para o GN, que também apresentou um menor equilíbrio funcional (p=0,001). A instabilidade ML foi correlacionada positivamente com o desequilíbrio funcional. Os resultados nos mostram uma alteração no sistema de controle postural na NDP, o que pode levar estes indivíduos a um maior risco a quedas e prejuízos funcionais.

Diabetic Peripheral Neuropathy (DPN) brings on reduced somatosensation, which can lead to changes in postural control. The objective of this study was to evaluate postural control in a standing position and in different conditions, as well as functional balance in individuals with DPN, make the correlation between the results obtained from the postural control assessment with the values from the functional balance test and compare the results obtained in the neuropathy group with those of the control group, checking for possible differences between the evaluation conditions of both groups. The study included 13 women with DPN (NG) and 17 non-diabetic women (CG). Postural control assessment was performed by kinemetry in the following conditions: eyes opened (EO), eyes closed (EC), and semi-tandem (ST). The data was processed in MATLAB and the following variables were generated: mean amplitude of oscillation (MAO) in the anterior-posterior (AP) and medial-lateral (ML) direction; and average speed of oscillation (ASO) in AP and ML direction. Functional balance was assessed by the Timed Up and Go Test. There was significant difference between the groups (p<0.005) in MAO-AP EO and EC, MAO-ML EC and ST, and ASO-ML ST. There were differences between the conditions EO and ST (p<0.005) and EC and ST (p<0.005) for the variables MAO-ML and ASO-ML with greater damage to the NG, which also had a lower functional balance (p=0.001). ML instability was positively correlated with functional imbalance. The results show a change in the postural control system in the DPN, which could lead these individuals to a higher risk for falls and functional impairment.
Controle postural e equilíbrio funcional em indivíduos com neuropatia diabética periférica
Keywords: Equilíbrio; Fisioterapia; Neuropatias diabéticas; Balance; Physiotherapy; Diabetic neuropathies